Intrinsic to extrinsic phonon lifetime transition in a GaAs-AlAs superlattice. - Hofmann, F; Garg, J; Maznev, A; Jandl, A; Bulsara, M; Fitzgerald, E; Chen, G; Nelson, K (2013)
We have measured the lifetimes of two zone-center longitudinal acoustic phonon modes, at 320 and 640 GHz, in a 14 nm GaAs/2 nm AlAs superlattice structure. By comparing measurements at 296 and 79 K we separate the intrinsic contribution to phonon lifetime determined by phonon-phonon scattering from the extrinsic contribution due to defects and interface roughness. At 296 K, the 320 GHz phonon lifetime has approximately equal contributions from intrinsic and extrinsic scattering, whilst at 640 GHz it is dominated by extrinsic effects. These measurements are compared with intrinsic and extrinsic scattering rates in the superlattice obtained from first-principles lattice dynamics calculations. The calculated room-temperature intrinsic lifetime of longitudinal phonons at 320 GHz is in agreement with the experimentally measured value of 0.9 ns. The model correctly predicts the transition from predominantly intrinsic to predominantly extrinsic scattering; however the predicted transition occurs at higher frequencies. Our analysis indicates that the 'interfacial atomic disorder' model is not entirely adequate and that the observed frequency dependence of the extrinsic scattering rate is likely to be determined by a finite correlation length of interface roughness.